2020
DOI: 10.1186/s40663-020-0218-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial pattern and driving factors of biomass carbon density for natural and planted coniferous forests in mountainous terrain, eastern Loess Plateau of China

Abstract: Background: Understanding the spatial pattern and driving factors of forest carbon density in mountainous terrain is of great importance for monitoring forest carbon in support of sustainable forest management for mitigating climate change. Methods: We collected the forest inventory data in 2015 in Shanxi Province, eastern Loess Plateau of China, to explore the spatial pattern and driving factors of biomass carbon density (BCD) for natural and planted coniferous forests using Anselin Local Moran's I, Local Get… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…However, in contrast, lower biomass at high elevation ranges was also documented by several workers [69][70][71]. Sun et al [72] reported a strong positive relation (R 2 = 0.67) of ABG biomass with elevation in the central highland, Vietnam. Furthermore, the findings of Li et al [19] exposes no significant interaction of altitude with vegetation carbon stock in Chitteri reserve forest.…”
Section: Discussionmentioning
confidence: 72%
“…However, in contrast, lower biomass at high elevation ranges was also documented by several workers [69][70][71]. Sun et al [72] reported a strong positive relation (R 2 = 0.67) of ABG biomass with elevation in the central highland, Vietnam. Furthermore, the findings of Li et al [19] exposes no significant interaction of altitude with vegetation carbon stock in Chitteri reserve forest.…”
Section: Discussionmentioning
confidence: 72%
“…The shrub and herb characteristics were measured from three randomly selected 2 m × 2 m quadrats in each plot. The biomass carbon density (BCD) (Mg/ha) of individual living trees for each forest plot was estimated using the biomass expansion factor (BEF) method [32,37]. The BCD of the shrub, herb, or litter layer for the forest-present plot was obtained by multiplying the biomass (Mg/m) by carbon content, which was 0.4627, 0.3270, and 0.4700 for the shrub, herb, and litter layers, respectively [32].…”
Section: Forest Inventory Datamentioning
confidence: 99%
“…We collected the dataset of annual mean temperature (TEMP) and annual mean precipitation (PRCP) for the period 1981-2015 at all these stations from the meteorological database of the scientific data platform of Shanxi Province. We then used the regression-kriging interpolation method [37][38][39] to derive the climatic data for each plot from that for each meteorological station, which combined regression of the climatic variable on topography variables (slope degree, slope aspect, and slope position) with kriging of the regression residuals [40]. We finally further corrected the derived TEMP for each sample plot according to the differences between the plot elevation and the interpolated elevation using the temperature lapse rate of 4.89 • C km −1 as the correction factor [33,37].…”
Section: Climate Datamentioning
confidence: 99%
“…The biomass carbon density (BCD) (Mg/ha) of individual living trees for each forest plot was estimated using the biomass expansion factor (BEF) method (Sun et al, 2020;Wang et al, 2018). The BCD of the shrub, herb, or litter layer for the forest-present plot was obtained by multiplying the biomass (Mg/m) by carbon content, which was 0.4627, 0.3270, and 0.4700 for the shrub, herb, and litter layers, respectively (Wang et al, 2018).…”
Section: Forest Inventory Datamentioning
confidence: 99%
“…We collected the dataset of annual mean temperature (TEMP) and annual mean precipitation (PRCP) for the period 1981-2015 at all these stations from the meteorological database of the scienti c data platform of Shanxi Province. We then used the regression-kriging interpolation method (Lamsal et al, 2011;Plouffe et al, 2015;Sun et al, 2020) to derive the climatic data for each plot from that for each meteorological station, which combined regression of the climatic variable on topography variables (slope degree, slope aspect, and slope position) with kriging of the regression residuals (Eldeiry and Garcia, n.d.). We nally further corrected the derived TEMP for each sample plot according to the differences between the plot elevation and the interpolated elevation using the temperature lapse rate of 4.89°C km −1 as the correction factor (Sun et al, 2020;Wang, 2014).…”
Section: Climate Datamentioning
confidence: 99%